1998
DOI: 10.1017/s1355838298981158
|View full text |Cite
|
Sign up to set email alerts
|

Spb4p, an essential putative RNA helicase, is required for a late step in the assembly of 60S ribosomal subunits in Saccharomyces cerevisiae

Abstract: Spb4p is a putative ATP-dependent RNA helicase that is required for synthesis of 60S ribosomal subunits. Polysome analyses of strains genetically depleted of Spb4p or carrying the cold-sensitive spb4-1 mutation revealed an underaccumulation of 60S ribosomal subunits. Analysis of pre-rRNA processing by pulse-chase labeling, northern hybridization, and primer extension indicated that these strains exhibited a reduced synthesis of the 25S/5.8S rRNAs, due to inhibition of processing of the 27SB pre-rRNAs. At later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 45 publications
(28 reference statements)
2
29
0
1
Order By: Relevance
“…Sucrose gradients were analysed using an ISCO UA‐6 system with continuous monitoring at A 254 . When required, fractions of 0.5 mL were collected from the gradients and proteins were extracted and analysed by western blotting as described .…”
Section: Methodsmentioning
confidence: 99%
“…Sucrose gradients were analysed using an ISCO UA‐6 system with continuous monitoring at A 254 . When required, fractions of 0.5 mL were collected from the gradients and proteins were extracted and analysed by western blotting as described .…”
Section: Methodsmentioning
confidence: 99%
“…When needed, fractions of 0.5 ml were collected from the gradients; protein and RNA were extracted from the different fractions as exactly described [70], and analysed as described below by northern or western blot analyses.…”
Section: Methodsmentioning
confidence: 99%
“…It was further demonstrated that in one of the loci, the RNA HELICASE 18 ( RH18 ) gene was required for the observed hybrid chlorosis phenotype. The function of RH18 is still uncharacterized in plants, but its homolog in yeast is known to be involved in 25S rRNA precursor processing (Cruz et al ., ). These studies suggest that in addition to rapidly evolving genes, highly conserved genes can also contribute to hybrid incompatibilities.…”
Section: Hybrid Incompatibilities Caused By Interactions Between Genementioning
confidence: 97%